2010
DOI: 10.1200/jco.2010.29.8216
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib-Melphalan-Prednisone-Thalidomide Followed by Maintenance With Bortezomib-Thalidomide Compared With Bortezomib-Melphalan-Prednisone for Initial Treatment of Multiple Myeloma: A Randomized Controlled Trial

Abstract: VMPT followed by VT as maintenance was superior to VMP alone in patients with multiple myeloma who are ineligible for autologous stem-cell transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
323
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 395 publications
(342 citation statements)
references
References 33 publications
14
323
2
3
Order By: Relevance
“…In contrast, as reported in other recent studies, overlapping toxicities may significantly increase the rate of AEs, such as those seen with VDCR, but may also contribute to less than expected efficacy results of regimens, presumably due to treatment delays and discontinuations. 15,16,25 The results presented herein further validate the very high quality of responses seen with the RVD regimen. 6,15,16,26 Furthermore, our results suggest that the addition of a fourth drug, specifically PLD, may improve the depth and duration of response for all patients compared with RVD.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In contrast, as reported in other recent studies, overlapping toxicities may significantly increase the rate of AEs, such as those seen with VDCR, but may also contribute to less than expected efficacy results of regimens, presumably due to treatment delays and discontinuations. 15,16,25 The results presented herein further validate the very high quality of responses seen with the RVD regimen. 6,15,16,26 Furthermore, our results suggest that the addition of a fourth drug, specifically PLD, may improve the depth and duration of response for all patients compared with RVD.…”
Section: Discussionsupporting
confidence: 58%
“…31 In more recent results, differences in overall response rates and CR for VMPT-VT vs VMP were statistically significant (P ϭ .01 and P Ͻ .001, respectively). 25 This study also reported a 3-year PFS benefit (median follow-up 23.2 months; VMPT-VT 56% vs VMP 41%; P ϭ .008). This difference reflected both the superior depth of response to initial cytoreduction and the significant maintenance effect with bortezomib and thalidomide, which was limited to the VMPT-VT arm.…”
Section: Discussionmentioning
confidence: 66%
“…The neuropathy with bortezomib can occur abruptly, and can be significantly painful and debilitating in a subset of patients. Recent studies show that the neurotoxicity of bortezomib can be greatly diminished by administering bortezomib using a once-weekly schedule [65,66], and by administering the drug subcutaneously [67]. Unlike lenalidomide, bortezomib does not appear to have any adverse effect on stem cell mobilization [68].…”
Section: Risk-adapted Therapymentioning
confidence: 99%
“…Neuropathy is a significant risk with VMP therapy when bortezomib is administered in the usual twice weekly schedule; Grade 3 neuropathy occurred in 13% of patients versus 0% with MP [78]. This rate can be greatly decreased by administering bortezomib using a once-weekly schedule [65,66]. VCD can be considered as a minor modification of the VMP regimen, in which cyclophosphamide is used as the alkylating agent in place of melphalan.…”
Section: Options For Initial Treatment In Patients Not Eligible For Asctmentioning
confidence: 99%
“…[1][2][3] Immunomodulatory drugs (IMiDs; thalidomide and lenalidomide) and proteasome inhibitors (PIs; bortezomib) significantly improved survival in transplant-eligible and -ineligible patients. [4][5][6][7][8][9][10][11][12][13][14][15] Given the survival rate in transplant-ineligible patients and the substantial toxicity of high-dose melphalan (melphalan 200 mg/m 2 [MEL200]), the role of ASCT has become an area of debate, and the comparison with less toxic, oral novel agentsbased treatments a high research priority. Cyclophosphamide-lenalidomide-dexamethasone (CRD) showed a partial response rate of 85% and a good safety profile.…”
Section: Text Word Count (Max 3000): 2999 Introductionmentioning
confidence: 99%